THE PORTRAIT OF TEACHING ENGLISH AS A FOREIGN LANGUAGE FOR YOUNG LEARNERS - Fetty Poerwita Sary (University of Kuningan, 2012)
Abstract: ThisÂ observational study focuses on strategies used by teachers when teaching English as a Foreign Language to private international primary school students. This study attempted to address the following question: whatÂ instructional strategies are used by the English teachers at this school? The data collected by using aÂ classroom observation and interview with teachers and students, were analyzed qualitatively by using categories formulated based on theories related toÂ instructional strategies includeÂ planning and preparing the instruction, implementing the teaching andÂ learning process, and assessing the studentsâ€™ achievement. The major ï¬ndings of this study include 1) although the teachers do the same stages in planning but the plan is implemented and resulted in different ways; 2) the teachers are able to use games as a tool for learning; 3) although curriculum requires teachers to integrate the skills (reading, listening, writing, and speaking), in actual implementation, the teachers do not teach English in integrative ways; 4) time management in this school has become a problematic factor for the teachers; 5) with respect to teacherâ€™s strategies in assessing studentsâ€™ achievement, the teachers doÂ assessment by way of remedial teaching once a week after the class is over in part where the students failed to understand. Keywords:Â teaching English as a foreign language (EFL),Â learning process, teaching strategies,Â instructional strategies,Â assessment.